Stratigraphic Analysis of Gercus Formation in Dohuk area, Northern Iraq - Awad, Karrar Hassooni; Alsultan, Hamid Ali Ahmed (Iraqi Journal of Science, 2020)
A surface section of the Gercus Formation (Middle-Late Eocene) was studied in Berafat area, Dohuk Governorate, Northern Iraq. The Gercus Formation consists of a mixed siliciclastic sediments, evaporates and carbonate sequences in the studied region, predominantly in the upper and middle parts. Nevertheless, it usually consists of upward-fining carbonate-rich sandstone cyclothems, marl, conglomerate and siltstone along with a gypsum lens and thin micrite carbonate beds. The Gercus Formation was deposited in delta and delta front of occasionally depositional environment which is represented by red-brown claystone and reddish-brown mudstone lithofacies. Cross bedded pebbly sandstone, trough cross-bedded sandstone and laminated cross-bedded sandstone lithofacies are deposited in braided delta environment. Marl lithofacies and gypsum lithofacies are deposited in intertidal and supratidal environments. The sea level fluctuation caused the river base level to occasionally rise and fall. In addition, the process changed from erosion to deposition, while the grain size also changed at different environments from gravel to sand and clays. The Gercus succession of northern Iraq was developed during the Middle-Late Eocene in an active margin basin, where the last stage closure of the New-Tethys and its collision with the Eurasian plate took place between the northeastern Arabian plate. It caused major episodes of uplifts and subsidence along with base level variations due to eustatic ups and downs. Within Gercus Formation, several fourth order cycles can be recognized, reflecting generally asymmetrical cycles, as well as the difference between sediment supply and accommodation space.